Framing Design to support Social Innovation: The Open4Citizens Project. (28th July 2017) - Morelli, Nicola; Aguilar, Marc; Concilio, Grazia; Götzen, Amalia De; Mulder, Ingrid; Pedersen, Janice; Torntoft, Louise Klitgaard
Abstract: In the recent years, new forms of organization have emerged, that have a disruptive power over the existing social and economic system. This phenomenon is challenging the traditional design approach, based on the idea that designers could design services for citizens and public administrations. In the new processes designers and service provider are simply mediating the process of co-creation and supporting the ecosystem for the value creation process. This paper will propose a logical framework for the design action, according to a multi-level structure that includes the value-creation level, in which design is a prerogative of the stakeholders participating in the value-creation action; the level of infrastructuring in which designers use their expert knowledge to support the interaction in the value-creation phase; and the level of governance, in which designers must figure out the structure of the ecosystem in which the value-creation process can be adequately organized and possibly scaled-up.